The last romantics a novel - Conklin, Tara (New York, NY : HarperLuxe, an imprint of HarperCollinsPublishers, 2019)
When she is asked about the inspiration behind her iconic work, renowned poet Fiona Skinner recounts the summer her family spent in a middle-class Connecticut town.
"Larger print"--Spine.
Keywords: Brothers and sisters -- Fiction; Large type books; Connecticut -- Fiction; Domestic fiction